SAT0544 Entheseal Involvement in Asymptomatic HIV Patients: An Ultrasonographic Study. (15th July 2016) - Ciancio, G.; Sghinolfi, L.; Furini, F.; Segala, D.; Farina, I.; Galuppi, E.; Bonazzi, S.; De Stefani, E.; Libanore, M.; Govoni, M.
Abstract : Background: A complex variety of musculoskeletal manifestations have been described in HIV patients, including conditions belonging to the wide spectrum of spondyloarthropathies (SpA). Enthesitis is a distinctive feature of SpA. Peripheral enthesitis is usually revealed by clinical findings but it may also be asymptomatic and detected only by imaging, such as conventional radiography, magnetic resonance or ultrasonography (US). Objectives: The aim of the present study was to evaluate by US examination the prevalence of enthesitis in patients with HIV infection without rheumatic clinical symptoms in comparison with control healthy subjects. Methods: 28 patients with aymptomatic HIV infection (22 M and 6 F; mean age:43 ± 8.6) were consecutively examined with US (Toshiba- Aplio XG- 12–18 MHz linear array transducer). All patients were recently diagnosed as HIV infected, didn't take any HIV treatment and had no clinical signs or symptoms of joint or enthesis involvement. 25 healthy subjects, matched for sex, age and BMI were studied as controls. The following sites were examined bilaterally by US: common extensor tendon insertion on the lateral epicondyle of the humerus; quadriceps tendon insertion on the superior pole of the patella; patellar tendon insertion (patellar ligament origin and the patellar ligament insertion at the tibial tuberosity); Achilles tendon insertions on the calcaneus. The following abnormal findings were recorded: thickness, bony erosions, enthesophytes and bursitis. Local blood flow was examined using Power Doppler (PD) mode. US and PDUS were performed by an experienced operator and blinded to the clinical examination. Results: 20/28 HIV patients (71.4%) presented almost one enthesis abnormality in comparison with 3/25 (12%) healthy controls (p<0.05). In 17/28 (60.7%) HIV patents was evidenced thickness; in 15/28 (53.5%) bursitis; in 13/28 (46.4%) enthesophytes and in 4/28 (14.2%) erosions. PD was positive in 11/28 (39.2%) HIV patients. In healthy controls, US showed thickness in 2/25 (8%), enthesophytes in 1/25 (4%) and altered PD in 1/25 (4%). The intra and inter-reader agreements were high (>0.8 intra-class correlation variability). Conclusions: US revealed a high frequency of subclinical enthesis abnormalities in asymptomatic HIV patients without rheumatic clinical signs and symptoms, highlighting the important role of US investigation and the strong association of HIV infection with rheumatic manifestations typical of SpA. References: Iordache L et al. Autoimmune diseases in HIV-infected patients: 52 cases and literature review Autoimmun Rev. 2014 Aug;13(8) Reveille D et al Rheumatologic complications of HIV infection. Best Practice & Research Clinical Rheumatology 2006; 20 Balint PV et al Ultrasonography of entheseal insertions in lower limb in spondylarthropathy. Ann Rheum Dis 2002;61 Disclosure of Interest: None declared